A long‐term field experiment of soil transplantation demonstrating the role of contemporary geographic separation in shaping soil microbial community structure - Sun, Bo; Wang, Feng; Jiang, Yuji; Li, Yun; Dong, Zhixin; Li, Zhongpei; Zhang, Xue‐Xian (Ecology and evolution, 2014)
The spatial patterns of microbial communities are largely determined by the combined effects of historical contingencies and contemporary environmental disturbances, but their relative importance remains poorly understood. Empirical biogeographic data currently available are mostly based on the traditional method of observational survey, which typically involves comparing indigenous microbial communities across spatial scales. Here, we report a long‐term soil transplantation experiment, whereby the same two soils (red Acrisol and purple Cambisol from Yingtan) were placed into two geographic locations of ~1000 km apart (i.e., Yingtan in the mid‐subtropical region and Fengqiu in warm‐temperate region; both located in China). Twenty years after the transplantation, the resulting soil microbial communities were subject to high‐throughput 454 pyrosequencing analysis of 16S and 18S rRNA genes. Additionally, bacteria and archaea involved in nitrogen cycling were estimated using clone library analysis of four genes: archaeal amoA, bacterial amoA, nirK, and nifH. Data of subsequent phylogenetic analysis show that bacteria, fungi, and other microbial eukaryotes, as well as the nitrogen cycling genes, are grouped primarily by the factor of geographic location rather than soil type. Moreover, a shift of microbial communities toward those in local soil (i.e., Chao soil in Fengqiu) has been observed. The results thus suggest that the historical effects persistent in the soil microbial communities can be largely erased by contemporary disturbance within a short period of 20 years, implicating weak effects of historical contingencies on the structure and composition of microbial communities in the soil. The relative importance of historical and contemporary factors in shaping microbial community structure was assessed in this work by a long‐term large‐scale soil transplantation experiment, whereby the same two soils (red soil and purple soil from Yingtan, China) were placed into two geographic locations of ~1000 km apart. Twenty years after the transplantation, the resulting soil microbial communities were subject to molecular analysis, including the high‐throughput 454 pyrosequencing of 16S and 18S rRNA genes. The results suggest that the historical effects persistent in the soil microbial communities can be largely erased by contemporary disturbance within a short period of 20 years, implicating weak effects of historical contingencies on the structure and composition of microbial communities in the soil.